2019
DOI: 10.31223/osf.io/awqjg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Accuracy of Watershed-Scale General Circulation Model Runoff Using Deep Neural Networks

Abstract: Projecting impacts of climate change on water resources is a vital research task, and general circulation models (GCMs) are important tools for this work. However, the spatial resolution of downscaled GCMs makes them difficult to apply to non-grid conforming scales relevant to water resources management: individual watersheds. Machine learning techniques like deep neural networks (DNNs) may address this issue. Here we use a DNN to predict monthly watershed-scale runoff (i.e., stream discharge divided by waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Because of its ability to simulate extremely complex and unknown processes, it has been widely used in water sciences. 17 Various researches have been conducted on the effect of land use and climate changes on water sources and the hydrological status of the watershed. For example, Marin et al 18 evaluate climate resource vulnerability due to climate change using the SWAT model, and based on the results of the analyses, a downward trend was observed for discharge at the end of the 21st century (up to 54%) and also a downward trend was observed for the surface flow up to 41%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its ability to simulate extremely complex and unknown processes, it has been widely used in water sciences. 17 Various researches have been conducted on the effect of land use and climate changes on water sources and the hydrological status of the watershed. For example, Marin et al 18 evaluate climate resource vulnerability due to climate change using the SWAT model, and based on the results of the analyses, a downward trend was observed for discharge at the end of the 21st century (up to 54%) and also a downward trend was observed for the surface flow up to 41%.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks are powerful tools that are made with the simple mimicry of the human biological nervous system. Because of its ability to simulate extremely complex and unknown processes, it has been widely used in water sciences 17 . Various researches have been conducted on the effect of land use and climate changes on water sources and the hydrological status of the watershed.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that different architectures could be a better fit for different watersheds. Similarly, Ghose (2019) compared ANNs and RNNs for the Dhankauda watershed of Sambalpur, Odisha, India and showed that RNNs outperformed ANNs for their data in monthly streamflow forecasts.In 2020,Rice et al (2020) trained a deep ANN with precipitation, evapotranspiration, and temperature for 2,731 watersheds in the conterminous United States. They compared their method to some machine learning algorithms such as SVMs, linear regression, and extreme gradient boosting.…”
mentioning
confidence: 99%